2008
DOI: 10.48550/arxiv.0809.0751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$B_d-\bar{B}_d$ mixing vs. $B_s-\bar{B}_s$ mixing with the anomalous $Wtb$ couplings

Jong Phil Lee,
Kang Young Lee

Abstract: We explore the effects of the anomalous tbW couplings on the B d − Bd mixing and recently measured Bs − Bs mixing. The combined analysis of mixings via box diagrams with penguin decays provides strong constraints on the anomalous top quark couplings. We find the bound from the B d − Bd mixing data is stronger than that from the Bs − Bs mixing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the present paper we consider anomalous tW d j interactions as a possible solution of these anomalies via their contribution to B d,s − Bd,s mixing amplitudes. Similar analyses have been attempted recently [9,10] using a subset of all possible effective tW d j operators. In particular, the authors of [9] have constrained contributions of two possible tW b operators using mostly B d oscillation parameter measurements, while in Ref.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In the present paper we consider anomalous tW d j interactions as a possible solution of these anomalies via their contribution to B d,s − Bd,s mixing amplitudes. Similar analyses have been attempted recently [9,10] using a subset of all possible effective tW d j operators. In particular, the authors of [9] have constrained contributions of two possible tW b operators using mostly B d oscillation parameter measurements, while in Ref.…”
Section: Introductionmentioning
confidence: 76%
“…Similar analyses have been attempted recently [9,10] using a subset of all possible effective tW d j operators. In particular, the authors of [9] have constrained contributions of two possible tW b operators using mostly B d oscillation parameter measurements, while in Ref. [10] they considered two tW s operators and concluded that the large non standard CP violating phase in B s − Bs mixing can be accommodated without violating B → X s γ constraints provided that the two NP operator contributions conspire in a way to mostly cancel in the later process while at the same time significantly affect the former.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, the D0 collaboration announced the evidence for the charge asymmetry of the like-sign dimuon events [12]. For more discussions about B s -Bs mixing, see [13,14] and references therein.…”
mentioning
confidence: 99%